2016
DOI: 10.1007/s11356-016-6992-7
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effect of a binary mixture of dicamba- and glyphosate-based commercial herbicide formulations on Rhinella arenarum (Hensel, 1867) (Anura, Bufonidae) late-stage larvae

Abstract: The acute toxicity of two herbicide formulations, namely, the 57.71 % dicamba (DIC)-based Banvel(®) and the 48 % glyphosate (GLY)-based Credit(®), alone as well as the binary mixture of these herbicides was evaluated on late-stage Rhinella arenarum larvae (stage 36) exposed under laboratory conditions. Mortality was used as an endpoint for determining acute lethal effects, whereas the single-cell gel electrophoresis (SCGE) assay was employed as genotoxic endpoint to study sublethal effects. Lethality studies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…The team reports that both glyphosate and GBHs increase the frequency of micronuclei formation. Soloneski et al [45] conducted a study in toads comparing the genotoxic impacts of a GBH, a dicamba-based herbicide, and a combination of these two, formulated herbicides, and concluded that the combination of GBH + dicamba herbicide led to a synergistic effect on the induction of primary DNA breaks. This result is worrisome given that well over one-half of the soybeans planted in the US in 2018 were genetically engineered to resist both GBHs and dicamba, and around two-thirds of national acreage will likely be sprayed in 2019 with this same mixture of herbicides [46,47].…”
Section: Genotox Studies Published Post-epa and Iarc Reviewsmentioning
confidence: 99%
“…The team reports that both glyphosate and GBHs increase the frequency of micronuclei formation. Soloneski et al [45] conducted a study in toads comparing the genotoxic impacts of a GBH, a dicamba-based herbicide, and a combination of these two, formulated herbicides, and concluded that the combination of GBH + dicamba herbicide led to a synergistic effect on the induction of primary DNA breaks. This result is worrisome given that well over one-half of the soybeans planted in the US in 2018 were genetically engineered to resist both GBHs and dicamba, and around two-thirds of national acreage will likely be sprayed in 2019 with this same mixture of herbicides [46,47].…”
Section: Genotox Studies Published Post-epa and Iarc Reviewsmentioning
confidence: 99%
“…Differential toxicity of glyphosate and its formulated PPPs have been also considered in the official scientific opinion by EFSA on pesticide risk assessment for amphibians and reptiles (Ockleford et al, 2018). Identification of acute lethal, physiological and genotoxic effects of glyphosatebased herbicides, including Roundup Original R and Roundup Transorb R , have continued on amphibians (Lajmanovich et al, 2011(Lajmanovich et al, , 2013(Lajmanovich et al, , 2014Yadav et al, 2013;Bellantuono et al, 2014;Levis and Johnson, 2015;Gandhi and Cecala, 2016;Rissoli et al, 2016;Soloneski et al, 2016) and reptiles (Latorre et al, 2013;Siroski et al, 2016). Teratogenic effects were reported in a treefrog (Scinax nasicus) (Lajmanovich et al, 2003) and in the embryo of the African clawed frog (Xenopus laevis) (Paganelli et al, 2010) in response to exposure to Glyfos R or Roundup Classic R at levels corresponding to 3-7.5 and 96-160 mg/l glyphosate concentrations, respectively.…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…The larvae reach up to 25 mm in length and are also easy to maintenance in the laboratory (Cei 1980). It is a widely studied species at the biochemical, physiological, and cytogenetic level, and it is frequently used in toxicity bioassays as a model species of ecotoxicological studies (Ferrari et al 2008;Pérez-Coll et al 2008;Brodeur et al 2009;Salinas et al 2015;Soloneski et al 2016;Attademo et al 2017).…”
Section: Test Speciesmentioning
confidence: 99%